2019
DOI: 10.1039/c9ta07331k
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Co–O hole transport materials: gap state assisted hole extraction with superior electrical conductivity

Abstract: An inorganic NiCoOx hole conductor was developed as an HTM for PSCs. The champion device yielded a PCE of 20.03%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…This is somehow similar to the mechanism proposed to explain the increase of p-type conductivity in Al 3+ doped NiO. 109 Besides several demonstrations of successful cobalt doping of NiO to increase the performances of PSCs, 95,110 a particularly exciting study by Hou et al 111 reported a mixed amorphous Ni-Co oxide (with Ni : Co 1 : 1, even though the formation of NiCo 2 O 4 cannot be discarded entirely), demonstrated as an efficient layer for 20% perovskite solar cells, paving the way for a broad family of mixed oxides as hole selective layers.…”
Section: Transition Metal Cation Dopingsupporting
confidence: 66%
“…This is somehow similar to the mechanism proposed to explain the increase of p-type conductivity in Al 3+ doped NiO. 109 Besides several demonstrations of successful cobalt doping of NiO to increase the performances of PSCs, 95,110 a particularly exciting study by Hou et al 111 reported a mixed amorphous Ni-Co oxide (with Ni : Co 1 : 1, even though the formation of NiCo 2 O 4 cannot be discarded entirely), demonstrated as an efficient layer for 20% perovskite solar cells, paving the way for a broad family of mixed oxides as hole selective layers.…”
Section: Transition Metal Cation Dopingsupporting
confidence: 66%
“…A reason behind this opposite behavior might be the different cobalt oxidation state obtained from the high‐vacuum cosputtering route, where only a single XPS peak for the Co 2p 3/2 peak is obtained, compared with solution‐processed Co:NiO, where Co 2p 3/2 is more complicated, pointing to the coexistence of 2+ and 3+ oxidation states, as reported by Lee et al [ 139 ] Hou et al explored a regime beyond the doping, investigating a mixed Ni‐Co (1:1) oxide. [ 145 ] Here, the coexistence of Co 2+ and Co 3+ in the mixed oxide (similarly to CoO x ) is evident and the work function is increased as in the works from Kaneko et al [ 146 ] and Xie et al [ 147 ] Along with Co 3+ , Fe 3+ has been reported to enhance the hole concentration (by a factor of 1.5) and hole mobility (by a factor of 2.5) of NiO NPs. [ 148 ]…”
Section: Transition Metal Oxides: Theoretical Investigations Of Electmentioning
confidence: 71%
“…Prior to other characterizations, we have firstly revealed the interaction mechanism between GO and (NiCo) 1− y Fe y O x NPs as well as the potential effect on the charge extraction and transfer behaviors from perovskite film. In comparison to other inorganic p ‐type semiconductors, NiCoO x displays great hole sensitivity owing to the presence of gap states and relatively high hole conductivity [25] . The incorporation of Fe atom into NiCoO x lattice further increases the hole concentration and enhances the electronic coupling with GO, which will be discussed in the following part.…”
Section: Figurementioning
confidence: 93%